The run for safety: Financial fragility and deposit insurance - Rajkamal Iyer; Thais Lærkholm Jensen; Niels Johannesen; Adam Sheridan (University of Copenhagen, Economic Policy Research Unit (EPRU), 2016)
We study a run on uninsured deposits in Danish banks triggered by a reform that limited deposit insurance coverage. Using a unique dataset with information about all individual accounts in Danish banks, we show that the reform caused a 50% decrease in deposits above the insurance limit in non-systemic banks, but a much smaller decrease in systemic banks which experienced less withdrawals from uninsured accounts, but also more openings of new uninsured accounts. Our results highlight the significant risks from a differential reallocation of uninsured deposits across banks and, in turn, the need for high insurance limits during a crisis.
Keywords: 330; Einlagensicherung; Bankenliquidität; Finanzsystem; Dänemark